THE DEVELOPMENT OF BUSINESS ANALYTICS-BASED PERFORMANCE MANAGEMENT SYSTEM FOR EYE HOSPITAL ORGANIZATIONS - Renaldi Tibyan, Reno
Businesses in the healthcare sector have been facing competition and complexity, such as the decision to seek or purchase health care and delivery of patient care. A healthcare organization should have a set of performance measures that can be used to improve performance. An eye hospital, which empowers its performance management system (PMS) to provide performance information, can effectively and efficiently manage its organizational performance. The successful implementation of a PMS will provide effective support to management processes. However, some empirical studies found that inadequate data and poor data quality caused the unsuccessful implementation of PMS. There is also a growing need to accommodate data analysis capability in the practiced PMS. The PMS requires an appropriate framework that provides essential guidelines for its implementation. Many studies of performance management (PM) have been carried out. However, few previous studies on the topic of the development of PMS, which address business analytics capability, have been carried out in the context of the eye hospital organization. A preliminary study showed that a case organization needs a PM framework that can guide the implementation of a PMS and needs a system that is capable of analyzing performance information. This research aims to develop a suitable PM framework for eye hospital organizations, determine the indicators for measuring the performance of eye hospital organizations, and ensure that a PMS can capitalize the capability of business analytics to perform business information analysis. This study reviewed some referenced literature to identify the state-of-the-art of PM framework for supporting the PMS implementation. Some frameworks are already applied in the healthcare sector, such as Regulation and Quality Improvement Authority’s Performance Management Framework and Public Health Performance Management Framework. Generally, the reviewed frameworks represent a specific perspective or theme, such as the Balanced Scorecard that promotes a strategic management perspective. Some others reflect a context-specific perspective, such as Knowledge-Based Performance Management Framework that offers a knowledge-based approach and Multilayer Performance Management Framework which accommodates a business analytics approach. This study used a compare and contrast method to identify some gaps among the identified frameworks based on some considered aspects that are relevant to the development of an appropriate PM ii framework. The method recognized the proposed framework as the most considered PM framework to fulfill the gaps. The proposed framework uses a combined approach between PM processes and business analytics capability. Some constructs and measures were derived from the literature to compose a causal model of PM framework. These theoretical concepts were verified in a field study using a single case study method. The verification defined the content validity of the developed conceptual PM framework. The model links six latent exogenous variables to six latent endogenous variables. The primary outcome variable of this model is a performance improvement. Another causal model was developed to represent relationships between the observed variables and factors composing a suitable PM framework. The research methods used in this study were case study to verify the theorized variables of PM framework, survey to test the developed models, and archival study to gather information relevant to PM practice and the development of a PMS prototype. This research used a sequential exploratory approach combined with a confirmatory approach as the purpose of the inquiry. It employed a mixed approach of both quantitative and qualitative research methods. Focus group discussion/interview and questionnaires were used as data collection instruments in the study. A single case study was carried out at a national eye center as a case organization. The empirical tests were conducted at three nationally accredited eye hospitals. The findings of the study show that several factors, which are leadership, planning, execution, monitoring, communication and learning, evaluation, and improvement, construct a PM framework for eye hospital organizations. The findings show that almost all performance indicators that are sourced from the practice of the National Eye Center and two empirical studies have been confirmed and are “necessary” to be used by the surveyed eye hospitals. This study also ensures that the developed a PMS prototype can show capabilities to manage business performance and monitor organizational performances of the National Eye Center. This study has a limitation in strengthening the external validity of the developed theory or the proposed model. It needs multiple-case studies in the same settings at the other eye hospitals and further quantitative based study to replicate the findings. Based on the findings, key the managerial implications of this study are the surveyed eye hospitals need to evaluate the current PM practice and the management of each eye hospital needs to consider comprehensive processes and complete aspects of the PM framework to support the PMS implementation. This study has some contributions (scientific, practical, and contextual) to the development of PM research in the healthcare sector in the national context.